Analisis Faktor- Faktor Yang Mempengaruhi Keputusan Masyarakat Menjadi Nasabah (Studi Pada PT. Bank Pembiayaan Rakyat Syariah Gebu Prima Medan) - Sabda Wati (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This research was conducted with the aim of analyzing the factors that influence the community to become customers in choosing mudharabah financing at PT. BPRS Gebu Prima Medan. The research method used in this study was quantitative research and data collection techniques in this study used questionnaires. The data analysis used in this research is data quality test, classical assumption test, multiple linear regression test, and hypothesis testing. Based on the results of the study, it shows that internal factors (X) have a positive and significant influence on mudharabah financing decisions (Y), and external factors (X)) do not have a positive and significant influence on mudharabah financing decisions ( Y). the results of the (partial) t test obtained a sig value of 0.008 <0.05, therefore the provisions of the (partial) t test can be concluded that the hypothesis Ho is rejected and Ha is accepted, which means that partially the internal factor ( X) influences the mudharabah financing decision (Y).